New anticancer drugs from naturally derived products : a study on growth inhibition of leukemic cells using design of experiments approach. - Cheong, Kenneth Theng Wan. (2010)
Natural plant extracts have exhibited anticancer properties in research over the years, but drug screening is often tedious and slow. With the use of the classical one-factor-at-a-time (OFAT) method, a huge amount of resources is required when many drugs are involved. Understanding drug interactive effects is also vital in formulating the best drug combination for anticancer treatments, but this is not well understood from the OFAT method. In this study, the Design of Experiments (DoE) approach was applied to provide information on drug screening and drug interactive effects. Theaflavin, Epigallocatechin gallate (EGCG), Epicatechin (EC), Apigenin, Quercetin, Chrysin and Tannic Acid were seven known antileukemia natural plant extracts examined on their growth inhibitory effects on K562 cells over 48 hours at concentrations of 10μM and 100μM, using the Resolution III-Foldover-Semifold method. Experimental data was processed with Design-Expert 7 software by Stat-Ease, Inc. Results showed that for drug screening, Tannic Acid exhibited the strongest growth inhibitory effects on K562 cells. For drug interactive effects, the strongest growth inhibitory effects on K562 cells was achieved at high concentration of EGCG and low concentration of Tannic Acid. It was concluded that the DoE approach exhibited higher efficiency by requiring only 24 experimental runs, instead of 128 runs by OFAT.